RECONSTRUCTION OF SHARIA LAW ENFORCEMENT IN ISLAMIC BANKING BY THE SHARIA SUPERVISORY BOARD USING A SWOT ANALYSIS APPROACH - Mahipal, Mahipal; Wahyudin, Yudi (Indonesia Law Review, 2024)
The implementation of sharia principles in Islamic banking management has not always benefited. A challenge lies in the fact that the Sharia Supervisory Board's (SSB) oversight of Islamic banking has not operated at peak efficiency. Developing plans and policies for SSB's rehabilitation in Islamic banking management is the goal of this study. The literature review method and SWOT analysis was used to conduct the research. The analysis's findings indicate that the most important factor influencing SSB's presence in an organization and the management structure of Islamic banking is the frequency with which organizational internal factors—weaknesses (1.00) and strengths (0.95) of SSB—occur. Threats (0.24) and opportunities (0.56) from the external environment are supporting factors that can also influence SSB's existence. Furthermore, four methods for the reconstruction of the SSB were acquired. These strategies comprised: (i) rebuilding and repositioning sharia supervisory board in the Islamic banking, (ii) optimizing the sharia supervisory board's roles and function, (iii) reconstructing the institution of sharia supervisory board, and (iv) rebuilding Indonesia's sharia supervisory board's Islamic law. In an attempt to maximize the supervision built into Islamic banking in Indonesia, the four SSB construction concepts are anticipated to serve as a bridge.